Fusion of photogrammetry and coherence scanning interferometry data for all-optical coordinate measurement - Leach, Richard; Sims-Waterhouse, Danny; Medeossi, Fabrizio; Savio, Enrico; Carmignato, Simone; Su, Rong (Elsevier, 2018)
Multisensor data fusion is an approach to enlarge the potential applicability of measuring techniques and improve accuracy, taking advantage of the strengths of different techniques. In this work, we present a new method for the fusion of photogrammetry and coherence scanning interferometry (CSI) data. This method allows the photogrammetry data to be accurately scaled with reference to the CSI data, and in turn the exact locations of multiple CSI measurements can be determined in the coordinate system defined by photogrammetry. The culmination of this work is to allow for high-accuracy three-dimensional optical coordinate measurement and surface topography measurement simultaneously.